Análise do crescimento da infraestrutura de redes FTTH no Brasil e seus impactos: uma investigação sobre a expansão do uso da arquitetura de fibra óptica para o fornecimento de serviços de internet de alta velocidade - FARIAS JUNIOR, José Irinaldo Gomes de (2024)
In this article, an evaluation is presented on the performance and growth of FTTH (Fiber To The Home) networks in Brazil in recent years, with emphasis on the influence of the COVID-19 pandemic. The results point to a considerable increase in the implementation of FTTH networks during the pandemic period, driven by the increased demand for high-speed internet services and greater investment capacity in FTTH technologies, which of er greater stability and speed to telecommunications companies. Additionally, the article emphasizes the operation and advantages of FTTH connection, and also discusses the challenges and opportunities for the future development of these networks in Brazil.